Impact of User education programmes in the Library, University of Jaffna – an appraisal - Arulanantham, S.; Navaneethakrishnan, S. (13th Annual Research Symposium of the Faculty of Graduates Studies (FGS), University of Kelaniya, 2012)
Libraries function as the driving force in achieving the target of the universities and other higher educational institutions in the world. User education is considered as an important element of the services provided by any library. It includes various programmes of instruction, education and exploration provided by libraries to users to enable them to make more effective, efficient and independent use of information sources, services and facilities including formal and informal instruction delivered by a librarian or other staff member one-on-one or in a group. The goal of user education should be to improve the quality of users research output and ensure lifelong learning. User education programmes need continuous revision to keep up to date with the changing information environment. Also it is expected that written objectives for instruction should be derived from the written profiles of the information needs of the users. Even though user education programmes are carried out in Sri Lankan University libraries in the form of library orientation for first year students during the inauguration session of the faculties, lecturing is the most commonly used method being applied by most of the Universities for user education programmes. It is the common practice of the libraries to start the orientation with a short introduction followed by a round of the library. User education programmes are conducted by the Library, University of Jaffna in various forms. In general Library orientation lectures with library visit is conducted for the newly admitted students. It was extended as session programme for three weeks covering 20 hours with the responsible support from Faculty of management. Information Literacy development programme is conducted in the form Permanent exhibits at micro level in important corners of the reader services section covering user awareness, library orientation, bibliographic instruction and interest profiling which are the four components of user education programmes. An exhibition named as ‘Path to Knowledge’ was held as user education programme at macro level in 2009. Objective of the study is to asses the Impact of User education programmes in the Library, University of Jaffna. This research paper provides a basic understanding of impacts of the User education programmes of the library, University of Jaffna, based on the quantitative and descriptive analysis of the readers’ visits, opinions, feedbacks and the developments encountered after the programmes. The findings of the study shows that the remarkable (20%) increase in number of visit of readers, enrichment of their information literacy level, appreciation and collaboration of departments, development of library awareness and re-origination of documentation culture are the major impacts of the user education programmes of the Library, University of Jaffna.
Keywords: User education; User education-University of Jaffna; Orientation programmes; Reading promotion